Effect of long-term exposure to cadmium on the earthworm Eisenia fetida (Oligochaeta) : possible resistance - Prinsloo, Manfred Wilhelm (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.